(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The theme of the work With pen and lens - houses in memory of Nadežda Petrović is an attempt to contextualize the family house at Ratarska 32 in Belgrade, where Nadežda Petrović, the first painter of Serbian modernism, lived in the period between 1884 and 1915. Analyzing various sources, the house is seen as a place of influence on the creation of the identity and internationally known painting creativity of Nadežda Petrović, but also as the place of origin of the traditionally created, rich and significant art collection of the Petrović family. The focus of the second part of the work is the house at Ljubomira Stojanovića 25, in the Professor’s colony in Belgrade. As a legacy of Ljubica Luković, the sister of Nadežda and Rastko Petrović, this house was transformed into a memorial museum and the art collection of Nadežda and Rastko Petrović is supposed to be exhibited there. The specificity of the museum space, which unites movable and immovable cultural heritage - an art collection and a house as a legacy of family-related former owners, is the reason for considering that house from different perspectives. The aim of the work is to connect and analyze two Belgrade family houses through their historical origin and development, to confirm the thesis about the importance of the house as a home for the emergence of exceptional artist’s creativity and the potential of creating memorial museums on the former sites of everyday life. At the same time, it is a confirmation of the importance of the collective memory of the prominent civil families of Serbia in the 19th and 20th centuries through the institution of the museum as a space for memory and the specificity of a museum which, using memorial art collections, through memory establishes continuity between two eras - the time of the creation of art collections and their memory in a new space and time. The narrative of the second part of the work is illustrated with photographs, like one of the mediums of Nadežda Petrović’s artistic expression, with the aim of reminding societal institutions about the decay of the house at Ljubomira Stojanovića 25.